Investigation of the Rare Exclusive Bc*→Dsνν- Decays in the Framework of the QCD Sum Rules - V. Bashiry (Advances in High Energy Physics)
Exclusive Bc*→Dsνν- decay is studied in the framework of the three-point QCD sum rules approach. The two gluon condensate contributions to the correlation function are calculated and the form factors of this transition are found. The decay width and total branching ratio for this decay are also calculated.